(untitled) (Journal on Excellence in College Teaching, 2024)
Over the past 30 years, problem-based learning (PBL) has become a major force in health professions education and even in the broader educational world. This article focuses on the outcomes that have been found from using PBL in the health professions based on at least 20 reviews done since 1990. The outcomes identified in these reviews are described as well as the strength of the evidence used in their support. These review results are augmented with results from selected articles that elaborate on how PBL can produce the identified outcomes.